Heart rate variability in a patient after percutaneous renal denervation: a case report - Baksh, Taufiq M.; Bidikar, Mukta P. (International Journal of Research in Medical Sciences, 2017)
The overactivity of sympathetic component of autonomic nervous system is implicated in the genesis and progression of hypertension. We report the heart rate variability (HRV) of a patient after renal denervation for treatment of medically resistant hypertension. Catheter based renal denervation done for treatment of resistant hypertension reduces blood pressure by reducing the central sympathetic drive. In the present study we found a significant decrease in low frequency component of HRV in one month follow-up period after the procedure. We propose a simple, non-invasive 5-minute HRV could be a predictor of effective renal sympathetic denervation.